1993
DOI: 10.1088/0031-9155/38/8/012
|View full text |Cite
|
Sign up to set email alerts
|

The effect of lead underlying water on the backscatter of X-rays of beam qualities 0.5 mm to 8 mm Al HVT

Abstract: Direct measurement is made for X-ray beams with first-half-value thicknesses in the range 0.5 mm to 8 mm Al and for field sizes ranging from 15 mm diameter to 70 mm square at 100 mm SSD. The measurements were made in a water phantom using a 0.2 cm3 thimble ionization chamber. The surface dose relative to that for full backscatter conditions decreases as the depth of water with lead beneath decreases. Further, for a given thickness of water with lead beneath, the surface dose relative to that for full backscatt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
18
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 1 publication
2
18
0
Order By: Relevance
“…The acquisition of a new superficial treatment unit in our department, a Pantak SXT 150, prompted an independent measurement of dose reduction to confirm the clinical applicability of the previously published comprehensive data 1,2 . Differences between x-ray units in inherent filtration, x-ray tube design, treatment cone design, and peak potential mean that beams of the same nominal quality (i.e.…”
Section: Introductionmentioning
confidence: 80%
“…The acquisition of a new superficial treatment unit in our department, a Pantak SXT 150, prompted an independent measurement of dose reduction to confirm the clinical applicability of the previously published comprehensive data 1,2 . Differences between x-ray units in inherent filtration, x-ray tube design, treatment cone design, and peak potential mean that beams of the same nominal quality (i.e.…”
Section: Introductionmentioning
confidence: 80%
“…In their study they used x-ray beams with a HVL ranging from 0.5-8 mm Al and applicators with a treatment SSD of 10 cm. 7 They found that the surface dose decreased as the lead was positioned closer to the chamber.…”
Section: Introductionmentioning
confidence: 99%
“…In superficial radiotherapy, dose is prescribed to or near the skin surface and backscatter of radiation from underlying tissue contributes to that dose . Tissue backscatter is dominated by Compton interactions and the dependence of such backscatter on beam quality, SSD, and field size is well documented . Loss of backscatter radiation due to the presence of a lead, air or bone interface downstream from the surface has been investigated using experimental techniques that involve surface‐based ion chamber measurements as well as with a chamber at depth in a phantom .…”
Section: Introductionmentioning
confidence: 99%
“…Surface‐based ion chamber techniques measure backscatter reduction effects on surface dose. Such measurements have been restricted to a minimum surface‐interface separation ≈5 mm due to the chamber dimensions . This limitation is in part vindicated by the large number of clinical treatments that involve tissue with underlying lead or air at comparable or even greater depths.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation